2021
DOI: 10.29392/001c.29883
|View full text |Cite
|
Sign up to set email alerts
|

Using the Health Belief Model to explore rural maternal utilisation of skilled health personnel for childbirth delivery: a qualitative study in three districts of the Eastern Region of Ghana

Abstract: BackgroundAlthough maternal mortality has decreased substantially since the 1990s, it remains one of the top priorities in global health, as most deaths can be prevented if women have access to and utilise skilled health personnel for childbirth delivery. While efforts have been made to increase the supply and accessibility of services, the lack of maternal utilisation of skilled health delivery services is a contributing cause of death, particularly among mothers from rural areas. MethodsWe conducted intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The demographic, socioeconomic, and cultural variables (e.g., age, race, ethnicity, education, income) can influence behavior [ 51 ]. In a study, which employed the HBM’s constructs of perceived risk, self-efficacy, and cues to action, the likelihood of SBA deliveries among Ghanaian women was examined [ 52 ]. The authors reported that women whose deliveries were conducted by SBAs believed that they were prone to complications during childbirth, had high perceived self-efficacy to overcome barriers to deliver with SBAs, and were well-prepared to deliver with SBAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic, socioeconomic, and cultural variables (e.g., age, race, ethnicity, education, income) can influence behavior [ 51 ]. In a study, which employed the HBM’s constructs of perceived risk, self-efficacy, and cues to action, the likelihood of SBA deliveries among Ghanaian women was examined [ 52 ]. The authors reported that women whose deliveries were conducted by SBAs believed that they were prone to complications during childbirth, had high perceived self-efficacy to overcome barriers to deliver with SBAs, and were well-prepared to deliver with SBAs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that women whose deliveries were conducted by SBAs believed that they were prone to complications during childbirth, had high perceived self-efficacy to overcome barriers to deliver with SBAs, and were well-prepared to deliver with SBAs. In contrast, women who did not deliver with SBAs were less likely to believe in susceptibility to complications, had low perceived self-efficacy to overcome barriers, and were not prepared to deliver with SBAs in advance [ 52 ]. In our study it was found that women whose latest delivery was conducted by SBAs were more likely to seek ≥ 4 ANC, ≥ 4 PNC visits when compared with women whose latest delivery was not conducted by SBAs, and this suggests that these women were awareness of their susceptibility to complications and were preparing in advance during pregnancy to deliver with SBAs.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic, socioeconomic, and cultural variables (e.g., age, race, ethnicity, education, income) can in uence the behaviour (30). In a study, which employed the HBM's constructs of perceived risk, self-e cacy, and cues to action, the likelihood of SBA deliveries among Ghanaian women was examined (31). The authors reported that women whose deliveries were conducted by SBAs believed that they were prone to complications during childbirth, had high perceived self-e cacy to overcome barriers to deliver with SBAs, and were well-prepared to deliver with SBAs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that women whose deliveries were conducted by SBAs believed that they were prone to complications during childbirth, had high perceived self-e cacy to overcome barriers to deliver with SBAs, and were well-prepared to deliver with SBAs. In contrast, women who did not deliver with SBAs were less likely to believe in susceptibility to complications, had low perceived self-e cacy to overcome barriers, and were not prepared to deliver with SBAs in advance (31). Using the HBM, a study in Nigeria found that women's perceived susceptibility to complications during pregnancy and childbirth, including pre-eclampsia and eclampsia, in uences healthcare seeking behaviour (32).…”
Section: Discussionmentioning
confidence: 99%